Complexity Of Land Procurement Problems Sport Center In North Sumatera Province - Suhendi, Dadang (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
Since the Basic Agrarian Law (Law Number 5 of 1960) was enacted on September 24, 1960, it is expressly stipulated in Article 6 that land rights have social functions and this has become one of the principles in Indonesian Agrarian Law. Social functions are not only targeted at property rights, but all land rights, both private and public, as well as land rights must be devoted to the greatest prosperity of the people in accordance with the mandate of Article 33 paragraph (3) of the 1945 Constitution, and must be willing to give in taken by the State) if the public interest so desires.Theoretically, the social function of land is better known as originating from a State that adheres to a socialist notion which generally in its state constitution stipulates that all land parcels are managed by the State for the greatest prosperity of the people, meaning that land is recognized as common property of the people whose management is given to the State